Avaliação de desempenho no IFES campus Vila Velha : um instrumento (in)eficaz? - Almeida, Luanda Alves Britto de (2018)
Public administration has been subject to constant criticism regarding its efficiency, effectiveness and quality in the services provided. To follow this scenario of changes, it becomes necessary to create mechanisms in its management to act as a trainer of servers with skills and competence. Inserted in this context are the Federal Institutes of Education, which in compliance to Act n.º 11,091 of January 12, 2005, were forced to implement the performance evaluation as part of the process of development of technical-administrative in education (TAE) in the career. In this way, we sought to analyze the process of evaluating the performance of the technical-administrative servers at the Ifes – Vila Velha campus, with indicative possibilities of main actions that can guide to transform the current process into a management tool. This is a qualitative and quantitative research. All the necessary data were collected by semi structures interviews with managers and technical administrative employees of the campus and also documented researches. Based on the results of the interviews and researches, it was possible to consider that the current performance evaluation hardly contributes with the development of the institution and the technical administrative employees in relation to quality, professional qualification and work environment, placing the basically as a requirement for Progression by Merit with its financial effects. In order to contribute to the development process of the evaluation of the performance of the TAE employees, a set of actions is proposed at the end of the research aiming to make this procedure an instrument that brings about effective improvements of the human performance and, consequently, of the public service. The dissertation was developed in line with the line of research Operations Management in the Public Sector